Indigenous Medical Tradition and Biomedical Tradition: A Historical Relation of Hegemony - García Vázquez, Arlene Iskra (Advances in Social Sciences Research Journal, 2017)
The indigenous medical tradition is a system of knowledge, practices and beliefs about health-illness process, used by many social groups in Mexico, which has prevailed in a context marked by the epistemic, social and political hegemony of the biomedical tradition, a situation that has shaped its historical development, has impeded its recognition and appraisal as an effective and legitimate way to attend the health-illness process, and has been excluded from the official medicine. The above is the result of a historical process of long duration, which has its origins in the colonial era and was favored by the epistemic supremacy of science. This work analyzes the established relations, during the Spanish colonial era, between the indigenous and the Western medical traditions, to understand how that led to epistemic, social, political and institutional exclusion of the indigenous medical tradition. The historical stages of this study were established to identify the major events in the hegemony relationships among both traditions, which were analyzed based on the concepts of hegemony and tradition. The conclusion is that the hegemony relationships between the biomedical tradition and the indigenous medical tradition are the result of a historical and dynamic process of selection, reinterpretation and redefinition of cultural elements of the indigenous medical tradition, which involved the imposition of modern western culture’s concept of the world and of the epistemic criteria of science, as well as the establishment of institutions responsible of the control and regulation of the indigenous medical practice.